A study of characteristics of n-Mosfet and p-Mosfet by using PSPICE - 505583 Ashiqqin Shahrum,ld1987-; Abd. Rani Abd. Hamid; Fakulti Sains (2009)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2009